2014
DOI: 10.1159/000362205
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to the Viral Mimetic Poly I:C Alters Fetal Brain Cytokine Expression and Postnatal Behaviour

Abstract: An increased incidence of mental illness disorders is found in children and adolescents born to mothers who experienced an infection-based illness during pregnancy. Animal models to study the prenatal origin of such outcomes of pregnancy have largely used conventional rodents, which are immature (altricial) at birth compared with the human neonate. In this study, we used the precocial spiny mouse (Acomys cahirinus), whose offspring have completed organogenesis at birth, and administered a single subcutaneous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 89 publications
(119 reference statements)
1
36
0
Order By: Relevance
“…Antenatal infections are recognized as an important risk factor for adverse outcome in term and preterm neonates [27,28,29,30,31,32,33,34,35]. The combined exposure to perinatal inflammation and neonatal HI results in a complex interplay of various signaling pathways of which the exact underlying mechanism has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal infections are recognized as an important risk factor for adverse outcome in term and preterm neonates [27,28,29,30,31,32,33,34,35]. The combined exposure to perinatal inflammation and neonatal HI results in a complex interplay of various signaling pathways of which the exact underlying mechanism has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the spiny mouse ( Acomys cahirinus ), in which brain maturation at birth is relatively similar to term human infants, 5 mg/kg poly(I:C) at 20 days of gestation (term is 39 days) led to downregulation of tumor necrosis factor-α in the fetal brain, with behavioral abnormalities in sensorimotor function, social interaction, memory, and learning in the pups [42]. …”
Section: Rodent Models Of Infection/inflammation In Uteromentioning
confidence: 99%
“…In the poly I : C model, an increase in IL-1b is observed in the fetal brain 24 h after maternal injection [94] but TNF in the fetal brain is actually decreased 24 h after maternal poly I : C injection [68] and also in the neonatal brain [34]. This may be a fetal mechanism to adapt to the maternal immune activation and occurs through a-and b-crystallin downregulation of TNF [67].…”
Section: /2mentioning
confidence: 99%
“…Importantly, previous studies have indicated that TNF does not play a role in the early transmission of inflammatory signalling to the fetus [66,67] before post-natal development. Additionally, in the poly I : C model, TNF levels are reported to decrease initially in the fetal brain [34,67,68]. Hence, if TNF-mediated plasticity regulates the neurodevelopment of the MIA offspring, then this regulation would likely occur after the animal was born.…”
Section: Introductionmentioning
confidence: 99%